Generating New Meanings: Once Upon the Evolution of the Wundermärchen - Rania Hamsi; Wassila Hamza Reguig Mouro (International Journal of Social Communication, 2023)
Wondrous and continuously inviting readers to dwell in astonishment, the universe of fairytales is certainly full of marvelous facts. Displaying a long narrative of a passionate evolution in time, the enchantment genre celebrated its compassionate narratives by moving from oral tradition to literature, to the amazing world of cinema. Therefore, this research paper unveils the way this narrative institutionalized itself as a genre both in literature and cinema. The paper first traces the unique evolution of fairy tales from the oral to the written tradition; it then reveals the peculiar migration of the genre to the cinematic field accompanied with the nouveau uprise of the Twentieth Century cinematic genre and the Walt Disney Company.